Resonant dipole – dipole interaction of Rydberg atoms for realisation of quantum computations. (May 2018) - Beterov, I.I.; Khamzina, G.N.; Tret'yakov, D.B.; Entin, V.M.; Yakshina, E.A.; Ryabtsev, I.I.
Abstract: We report the application of the resonant dipole – dipole interaction of Rydberg atoms for the realisation of quantum computations with ultracold neutral atoms. Coherent population oscillations between the collective states of systems consisting of two interacting atoms make it possible to implement two-qubit phase gates, which are necessary for universal quantum computations. The schemes studied are alternatives to two-qubit gates based on the Rydberg dipole blockade effect. In contrast, the schemes we propose do not require large dipole – dipole interaction energies and can be realised for atoms that are at a considerable distance from each other. The bibliography includes 27 references.